Transfusion-free treatment strategies for acute anemia in critical care. Issue 8 (August 2016) - Morgan, Caitlin A.; Byul (Sarah), Sae; Forest, Christopher P.
Abstract : ABSTRACT: Acute anemia is a frequently encountered diagnosis in critically ill patients, and can be a challenge if blood products are not readily available or if patients refuse these products on the basis of their religious beliefs. This article discusses the goals of anemia management and summarizes several alternatives to blood transfusions that can be used to prevent and treat acute anemia.